Exportación de sulfato de aluminio de la cía. Quimpac Ecuador s.a al mercado de República Dominicana San Felipe de Puerto Plata - Maquilón Martínez, Arelis Beatriz (2016)
This project involves the exporting of aluminum sulfate s` Quimpac Ecuador Company S.A. to San Felipe of Puerto Plata - Dominican Republic. Aluminum sulfate is a solid white salt whose formula is Al2 (SO4) 3. Their physical properties are mainly used as a coagulating agent and primary flocculants in the treatment of water for human consumption, wastewater and use pool. It is characterized by grouping the suspended solids in the water and it accelerates settling, contributing to the reduction of bacterial load and removal of color and flavor…..